Global, regional, and national incidence and mortality for enteric infections from 1990 to 2019 - Bo Wang; Dongwei Chen; Hua Chen; Wei Wu; Kaiyi Cheng; Yixiu Tao; Ling Zhang; Ce Liu; Ding Ou; Mingxiu Zhang; Xianmei Tang; Shouli Wang; et al. (BMC Public Health)
Abstract Background Enteric infections are among the most common infectious diseases. The aim of this article was to track the global trends in morbidity and mortality from enteric infections in 204 countries or territories from 1990 to 2019. Methods Data were obtained from the Global Burden of Disease 2019 study. Average annual percentage changes (AAPCs) in age-standardized incidence rate (ASIR) and age-standardized mortality rate (ASMR) were calculated to quantify trends in enteric infections. Age-period-cohort models were used to estimate the annual percentage changes from 0 to 4 to 80 − 84 years (local drifts), period and cohort effects between 1990 and 2019 in different socio-demographic index (SDI) regions. Results In 2019, there were 6.59 billion incident cases of enteric infections, and caused 1,748,251 deaths worldwide. From 1990 to 2019, the trend in the global ASIR of enteric infections was relatively stable, but that of ASMR declined (AAPC=-3.30, 95% confidence interval [CI]: -3.54 to -3.07), and global mortality decreased in all age groups. Meanwhile, decreasing trends in ASMR were observed in 173 countries/territories (P < 0.05), particularly in North Macedonia and Kazakhstan. The low and low-middle SDI areas showed decreasing trends in ASIR and ASMR for enteric infections. However, an increasing trend was observed in high SDI regions, especially among older people aged over 60 years. Conclusions The global incidence of enteric infections did not change significantly between 1990 and 2019, but the mortality showed a significantly downward trend. The global burden of enteric infections remains serious in children under 5 years and in low and low-middle SDI regions.